Differentiating retirement age to compensate for health differences - Vandenberghe Vincent (Sciendo, 2021)
Population aging in Europe calls for an overall rise in the age of retirement. However, most observers agree that the latter should be differentiated to account for different individuals’ heterogeneous health when they grow older. This paper explores the relevance of this idea using the European Survey of Health, Ageing and Retirement in Europe (SHARE) panel data. It first quantifies the health gradient across and within each of the European countries across sociodemographic groups (i.e., Gender × Education) at typical retirement age. It then estimates the degree of retirement age differentiation that would be needed to equalize expected health at the moment of retirement. Results point at the need for a very high degree of differentiation to equalize expected health, both across and within, European countries. But the paper also shows that systematic retirement age differentiation would fail to match a significant portion of the full distribution of health status. In a world synonymous with systematic health-based retirement age differentiation, there would still be a lot of what health economists call F-mistakes ([F]ailure of treatment, i.e., no retirement for people in poor health) and E-mistakes ([E]xcessive treatment, i.e., people in good health going for retirement).